2018
DOI: 10.2298/gensr1801187j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combining ability and genetic components in sunflower

Abstract: prevalence of dominant component (H) compared to additive (D) and higher concentration of dominant genes (u) compared to recessive (v), in all investigated traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…They were significantly different from all other cross combinations but did not significantly differ themselves. The present study findings had similarity with following researcher findings for plant height Jocković et al (2018) andRukmini et al (2005).…”
Section: Plant Height (Cm)supporting
confidence: 91%
“…They were significantly different from all other cross combinations but did not significantly differ themselves. The present study findings had similarity with following researcher findings for plant height Jocković et al (2018) andRukmini et al (2005).…”
Section: Plant Height (Cm)supporting
confidence: 91%
“…Crosses showing highest 100-achene weight might be utilized in producing high yielding hybrids. Jocković et al (2018) and Khan et al (2008) had reported variability for 100-achene weight ranged from 5.51 to 10.50 g in sunflower. The abovementioned findings are in pars with these researchers.…”
Section: Achene Weight (G)mentioning
confidence: 96%
“…Combining ability of parental lines should be estimated to find the best hybrid combinations. Furthermore, estimation of gene effects could be done by analyzing combining ability values based on F 1 mean values (Jocković et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Jocić, Miladinović, & Kaya (2015) analyzed four male sterile lines and 10 testers and found additive gene effects for seed yield. However, Jocić, Miladinović, & Kaya (2015), Jocković et al (2018), and Makanda et al (2014) analyzed gene effects of inbred lines using line x tester method and they showed that non-additive gene effects were more important for seed yield. Larièpe et al (2017) also observed the after that gene component was more important than the additive component in managing seed yield in sunflower.…”
Section: Introductionmentioning
confidence: 99%